The effect of severe acute respiratory syndrome on emergency airway management - Wong, E. (Ann Emerg Med, 2004)
Study objectives: From early March 2003 to late May 2003, severe acute respiratory syndrome (SARS) was detected in Singapore. Two hundred thirty-eight patients were infected; 33 died. Forty-two percent were health care workers. The whole medical system in the country was put under stress. One major public hospital became the designated SARS hospital. Emergency cases were diverted to the remaining public hospitals, of which Singapore General Hospital was the main recipient. The increase in workload, new infection control procedures including mandatory wearing of the positive airway pressure respirator and personal protective equipment (PPE), and limiting the number of person-contacts with each patient were thought to affect resuscitation and airway management. Our aim is to study the effects of wearing of PPE and the restriction in number of resuscitation personnel on airway management during the SARS crisis. Methods: The emergency department has an ongoing airway registry that prospectively captures patient demographics, diagnosis, indications for intubation, persons and discipline of intubating physician, number of attempts, method of intubation, success rates, and complications. The data were divided into 3 periods: (1) before PPE was instituted from November 1, 2002, to March 31, 2003; (2) during SARS (when PPE use was mandatory) from April 1 to July 31, 2003; and (3) after SARs (when PPE use was nonmandatory but encouraged) from August 1 to December 31, 2003. Results: There was no change in patient demographics during the 3 periods, but there was a change in the patient diagnoses in period 2, with decreases in the proportion of respiratory and cardiac cases and increases in neurology and trauma cases. These changes reverted to the previous distribution in period 3. The alarming discovery was that whereas in period 1 (pre-SARS), resident medical officers attempted intubations 45% of the time, this figure went down to 35% in period 2 (SARS) and 23% in period 3 (post-SARS). Anesthetists performed 1.2%, 8%, and 0% of emergency intubations in periods 1, 2, and 3, respectively. Attending emergency physicians performed 54%, 56%, and 77% of intubations in periods 1, 2, and 3, respectively. The complication/peri-intubation event rates were 10.5%, 9.9%, and 9.4% in periods 1, 2, and 3, respectively. The success rate for residents was 80.8%, 89%, and 86.2% in periods 1, 2, and 3, respectively. Conclusion: The wearing of PPE and positive airway pressure respirator is thought to make intubation more difficult, as seen by the increase in proportion of intubations performed by anesthetists in period 2 and by attending emergency physicians in periods 2 and 3. The infection control policy that restricts the number of health care staff attending to each patient may have influenced the department's decision to allow only the most confident or experienced personnel to manage the airway. The exposure of junior residents in emergency airway management during SARS and the immediate post-SARS period was decreased. This trend should be further monitored, and intervention may be necessary should it continue to decline.